Has the Use of the Mask Exacerbated Rosacea During the Pandemic? - Ilaria Trave; Ilaria Salvi; Emanuele Cozzani; Rebecca Donadoni; Aurora Parodi (Mattioli1885, 2023)
Introduction: During the COVID-19 pandemic, personal protective equipment, particularly face masks, has become an essential requirement to engage in social activities. Several articles reported an increase of recurrences of dermatologic facial diseases (i.e., acne, rosacea) related to mask use. Objectives: To evaluate the number of recurrences of rosacea related to face mask use. Methods: This prospective study was conducted on adult patients with a pre-pandemic diagnosis of mild and moderate papulopustular rosacea. All patients had previously achieved either partial or complete remission after a 4-month treatment with ivermectin in 2019. We collected data in two different phases characterized by different intensity of mask use during the pandemic and post-pandemic period. We collected data through clinical assessment of the disease, questionnaires on personal habits and standardized skin surface biopsy to study the Demodex mites count. Results: We enrolled a total of 30 patients. In the pandemic period, 5/30 patients had a relapse of mild papulopustular rosacea; the Demodex sample resulted positive in 4/5 relapsed patients.  In the post-pandemic period, 4/30 patients reported a relapse of mild (3 patients) and moderate papulopustular rosacea (1 patient). At the Demodex exam, 1/4 relapsed patients resulted positive. Conclusions: We did not find a significant increase in relapses of papulopustular rosacea during the pandemic. An appropriate anti-parasitic treatment may reduce the number of recurrences due to mask use.